Interaction between age and blood urea nitrogen to creatinine ratio on mortality in patients with severe cirrhosis: a retrospective cohort study from the MIMIC database - Yi, Yu; Li, Lin; Chen, Yinghua; Luo, Yawen (Frontiers in Endocrinology, 2025)
BackgroundCirrhosis is a leading cause of global disease burden, with high mortality, particularly in critically ill patients. The blood urea nitrogen to creatinine ratio (BCR) is a straightforward biochemical indicator of renal excretory function and is linked to negative outcomes across different conditions. However, the relationship between BCR and mortality in critically ill patients with cirrhosis is unclear, The purpose of this study is to explore this question.MethodsA retrospective cohort study was performed utilizing the MIMIC-IV database. We divided BCR into quartiles and evaluated 180-day and 365-day mortality as the primary outcomes. Kaplan-Meier survival analysis and multivariate Cox regression modeling were used to assess the link between BCR and mortality. Linear relationships were further determined using restricted cubic spline (RCS) curves, and finally, subgroup analyses were also performed.ResultsIn our study of 2,816 critically ill cirrhotic patients, elevated BCR was significantly linked to higher mortality at both 180 and 365 days. The top BCR quartile showed a 45% higher risk of 180-day mortality (HR=1.45, 95% CI: 1.21-1.73) and a 38% higher risk of 365-day mortality (HR=1.38, 95% CI: 1.17-1.63) relative to the bottom quartile. RCS analysis demonstrated a notable linear correlation between BCR and mortality risk. Subgroup analyses indicated a stronger association between BCR and mortality among older patients.ConclusionIn critically ill cirrhotic patients, elevated BCR values are strongly linked to increased mortality risk. Our research highlights BCR’s potential as a prognostic marker for cirrhosis, especially in elderly patients.